New species of Harttia (Loricariidae, Loricariinae) from the Rio Sao Francisco Basin - Langeani, F.; Oyakama, O. T.; Montoya-Burgos, J. I. (Amer Soc Ichthyologists & Herpetologists, 2001)
A new species of the mailed catfish genus Harttia is described from the Sao Francisco River drainage, States of Minas Gerais and Bahia, Brazil. The new species is distinguished from congeners by the combination of an abdominal region covered by small bony plates; plates 3-4 times in eye diameter; interorbital width 3.1-4.0 in head length and greater than eye diameter; body width at anal fin origin 6.3-8.3 in standard length; margins of the head and pectoral fin spine of mature males with elongate and conspicuous odontodes; anal fin of males longer than of females. A key to Harttia species and a comparison with other species are provided.